Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1593/neo.10636
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of Oxidizable Proteins with a Photoactivatable Analog of the Antitumor Agent DMXAA: Evidence for Redox Signaling in Its Mode of Action

Abstract: The signaling pathway(s) and molecular target(s) for 5,6-dimethylxanthenone-4-acetic acid (DMXAA), a tumor vascular disrupting agent in late stages of clinical development, are still undefined. As an approach toward identifying potential targets for DMXAA, a tritiated azido-analog of DMXAA was used to probe for cellular binding proteins. More than 20 cytosolic proteins from murine splenocytes, RAW 264.7 cells, and the HECPP immortalized endothelial cells were photoaffinity-labeled. Although no protein domain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The Antioxidant DPI Diminishes DMXAA-mediated Signaling in Primary Macrophages-It has been shown previously that the antioxidant NAC inhibits DMXAA-mediated expression of cytokine genes such as Tnf in the macrophage cell line RAW 264.7 (43), suggesting that ROS could be regulating signaling in this pathway. Potential sources of cellular ROS in professional phagocytic cells are NADPH oxidases.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The Antioxidant DPI Diminishes DMXAA-mediated Signaling in Primary Macrophages-It has been shown previously that the antioxidant NAC inhibits DMXAA-mediated expression of cytokine genes such as Tnf in the macrophage cell line RAW 264.7 (43), suggesting that ROS could be regulating signaling in this pathway. Potential sources of cellular ROS in professional phagocytic cells are NADPH oxidases.…”
Section: Resultsmentioning
confidence: 96%
“…N-Acetylcysteine (NAC), the precursor of the cellular antioxidant glutathione, can be added to analyze the affects of oxidative stress. Previously, it has been shown that NAC treatment of the macrophage cell line RAW 264.7 decreases the expression of numerous cytokine genes such as Il6 and Tnf in response to DMXAA (43). This data suggests that antioxidants might also influence the expression of IFN-␤ in response to DMXAA.…”
Section: 6-dimethylxanthenone-4-acetic Acid (Dmxaa)mentioning
confidence: 85%
See 1 more Smart Citation
“…The NF- κ B signalling pathway (Joseph et al , 1999; Woon et al , 2003; Wang et al , 2006), the TBK1-IRF-3 signalling axis (Roberts et al , 2007), the NOD signalling pathway (Cheng et al , 2010), and at least three members of the MAPK superfamily (Sun et al , 2011) are involved in one or more of the pleiotrophic effects of DMXAA in mice. Studies from our own laboratory showed that more than thirty oxidisable proteins were photoaffinity labelled with an azido-analogue of DMXAA in cellular extracts from murine leukocytes, implicating a role for redox signalling (Palmer et al , 2007; Brauer et al , 2010). The yet unidentified cellular enzymes that catalyse the first-step, one-electron oxidation of DMXAA to form the benzyl radical initiating the generation of reactive oxygen species and redox signalling could also be regarded as biochemical target(s) for this class of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It can activate several inflammatory cell signaling pathways, including extracellular signal-regulated kinases 1 and 2, c-Jun N-terminal kinases, and cytosolic nucleotide-binding oligomerization domain 1 and 2-like receptors [4], [5]. In addition, DMXAA is a strong inducer of reactive oxygen species (ROS) [6]. The most striking immunogenic feature of DMXAA is its induction of immediate and predominant type-I-IFN [7].…”
Section: Introductionmentioning
confidence: 99%